Mapping nanometer and micrometer‐scale structures at graphite surface by photoelectron diffraction. (14th September 2018) - Fujita, Yoshiki; Ota, Hiroshi; Matsushita, Tomohiro; Muro, Takayuki; Senba, Yasunori; Matsui, Fumihiko
Abstract : A series of C 1 s photoelectron intensity angular distribution (PIAD) patterns from a crystalline graphite surface were mapped in two dimensions at intervals of 20  μ m. Two kinds of PIAD patterns rotated by 30° from each other, corresponding to the two domains from the twinned crystal, were found. The standard deviation of the diffraction contrast was evaluated for each PIAD pattern from its intensity histogram. Surprisingly, we found that odd‐number‐ (most probably single‐) atom‐height steps on the flat terrace region and their local atomic arrangement can be identified by two‐dimensionally mapping the standard deviation values. Furthermore, we analyzed the photoelectron diffraction patterns and noticed that the normal direction of the sample surface at each point was slightly inclined differently. By connecting all the inclination angle data, the micrometer‐scale corrugation of the sample surface was successfully visualized. Scanning photoelectron diffraction microscopy has been shown to be useful for the nanometer‐ and micrometer‐scale structural imaging.